Faktor Resiko Cedera pada Crossfit ditinjau dari Body Posture - Made Bagus Krishna Wiranatha; Putu Yudi Pramana Putra; Putu Ayu Sita Saraswati (Jurnal Syntax Admiration, 2024)
Crossfit is a sport that focuses on functional movements in everyday life with a mixture of various types of exercises with competitive and high intensity quickly and successively with limited rest time. High intensity exercise will put a very high risk of injury. To reduce this risk, it is important for practitioners to pay attention to body posture when doing exercises. The purpose of this study was to determine the risk factors for injury to crossfit in terms of body posture. The research method used is a literature review compiled based on secondary data in the form of research journal reviews obtained from databases spread on the internet related to risk factors for injury to crossfit in terms of body posture. Research journals are obtained from Google Scholar, Sage Journals, and springer links. By using keywords namely crossfit injury, sport body posture. Results: One of the factors that influence the occurrence of crossfit injuries is body posture. From several studies say that many crossfit practitioners are injured due to technical errors that cause loading in some parts of the body. Conclusion: Based on some of the literature discussed, it can be concluded that the risk of injury to crossfit practitioners can occur due to body posture and poor movement techniques from crossfit practitioners.